Multi-element bioimaging of Arabidopsis thaliana roots - Persson, Daniel Pergament; Chen, Anle; Aarts, Mark G.M.; Salt, David E.; Schjoerring, Jan K.; Husted, Søren (American Society of Plant Biologists, 2016)
Better understanding of root function is central for development of plants with more efficient nutrient uptake and translocation. We here present a method for multi-element bioimaging at the cellular level in roots of the genetic model system Arabidopsis thaliana. Using conventional protocols for microscopy we observed that diffusible ions such as potassium (K+) and sodium (Na+) were lost during sample dehydration. Thus, we developed a protocol which preserves ions in their native, cellular environment. Briefly, fresh roots are encapsulated in paraffin, then cryo-sectioned and freeze dried. Samples are finally analyzed by Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS), utilizing a specially designed internal standard procedure. The method can be further developed to maintain the native composition of proteins, enzymes, RNA and DNA, making it attractive in combination with other omics techniques. To demonstrate the potential of the method we analyzed a mutant of A. thaliana unable to synthesize the metal chelator nicotianamine (NA). The mutant accumulated substantially more zinc (Zn) and manganese (Mn) than the wild type in the tissues surrounding the vascular cylinder. For iron (Fe) the images looked completely different, with Fe bound mainly in the epidermis of the WT plants, but confined to the cortical cell walls of the mutant. The method offers the power of ICP-MS to be fully employed, thereby providing a basis for detailed studies of ion transport in roots. Being applicable to A. thaliana, the molecular and genetic approaches available in this system can now be fully exploited in order to gain a better mechanistic understanding of these processes.